PENGARUH MUATAN TRUK BERLEBIH TERHADAP BIAYA PEMELIHARAAN JALAN - M. Saleh, Sofyan; Z. Tamin, Ofyar; Sjafruddin, Ade; Bona Frazila, Russ (Jurnal Transportasi, 2009)
More than 90% of freight movement in Indonesia is carried out by land transportation (mostly highway mode). Meanwhile most nation land is surrounded by water, in which the movement could have been carried out by sea transportation. There are rail network in Java Island and some parts of Sumatera Island where multimodal/inter-modality system can be applied. However, lack of sea and rail transportation infrastructure and management makes highway mode the main choice among other transportation modes. This study investigated the impact of overloading trucks in the freight transportation system in Indonesia, because the government still allows trucks to carry up to 50% of the normal maximum load. This policy has greatinfluence on road deterioration, creating the vehicle damage factor approximately 5 times higher than that of the normal one. This overloading has a big impact on the maintenance of the road and will increase themaintenance budget.